A comprehensive review of flowshop group scheduling literature. (June 2016) - Neufeld, Janis S.; Gupta, Jatinder N.D.; Buscher, Udo
Abstract: Due to its practical relevance, the flowshop group scheduling problem has received much attention in the academic and practice-oriented literature. As machines are grouped to cells and parts to part families, this problem is also known as cellular manufacturing scheduling. Group scheduling is characterized by sequencing tasks on two levels: on the one hand, a sequence of part families has to be determined considering major family setup times while, on the other hand, a job sequence has to be found within each part family. Despite an increasing number of publications, no comprehensive review on group scheduling and its solution methods has been conducted so far. This paper intends to close this gap by reviewing the development of research and characterizing the considered problem. All publications are categorized regarding the number of machines, type of setup times as well as the solution approach. Furthermore, group scheduling in flexible flowshop environments as well as a related scheduling task in multiple cells, known as cell scheduling problem, is considered. Finally, open problems and promising fields for future research in the area of flowshop group scheduling are identified.